2004
DOI: 10.1182/blood-2003-02-0371
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution and lack of cytogenetic response are adverse prognostic factors for hematologic relapse of chronic phase CML patients treated with imatinib mesylate

Abstract: We followed 141 patients treated with imatinib mesylate (> 300 mg) for chronicphase chronic myelogenous leukemia (CML) following failure of treatment with interferon. During 12 months from the start of imatinib mesylate treatment, 96.5% achieved a complete hematologic response, 47.0% achieved a major cytogenetic response, and 32.4% achieved a complete cytogenetic response. The proportion of patients with hematologic relapse was 10.9% at 12 months and 14.6% at 18 months. In a univariate Cox regression analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 11 publications
3
62
1
4
Order By: Relevance
“…A failure to achieve MCR is associated with an increased risk of disease progression on imatinib. 32,33 Although the deletion status of the cohorts in which this progression is described is not known, the data are compatible with the reduced rate of MCR and increased risk of disease progression that we observed in our patients, both in CP and advanced phase CML.…”
Section: Discussionsupporting
confidence: 74%
“…A failure to achieve MCR is associated with an increased risk of disease progression on imatinib. 32,33 Although the deletion status of the cohorts in which this progression is described is not known, the data are compatible with the reduced rate of MCR and increased risk of disease progression that we observed in our patients, both in CP and advanced phase CML.…”
Section: Discussionsupporting
confidence: 74%
“…A prompt molecular response is also associated with longer progression-free survival. 4,21 The study has identified an expression profile associated with primary resistance. The classes of genes identified and the lack of mutations in the kinase domain of the bcr-abl gene suggest that this type of resistance is essentially BCR-ABL-independent.…”
Section: Discussionmentioning
confidence: 99%
“…2 Despite the high rate of response to imatinib therapy, the emergence of resistance to this treatment has been recognized as a major problem in the therapy of Phpositive CML patients. 3,4 Some important imatinib resistance mechanisms have been characterized, including mutations in the BCR-ABL domain and overexpression of BCR-ABL oncoprotein, [5][6][7][8] although these two mechanisms are associated with secondary or acquired resistance. Intrinsic resistance to imatinib has been linked to rapid drug efflux from hematopoietic cells and inactivation of imatinib by binding to serum a1-acid glycoprotein, 9 although supporting in vivo data are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Acute leukemia, in the absence of leukemogenic chemotherapy, evolves in less than 5% of patients, in direct contrast to CML. In CML, almost all patients develop a fatal acute leukemic phase usually in less than 5 years, but new targeted molecular therapies promise to greatly improve this situation [5,6].…”
Section: Introductionmentioning
confidence: 99%